Clause and predicative constituents in an Austronesian language: Lampung language - Afrianto; Sujatna Eva Tuckyta Sari; Darmayanti Nani; Ariyani Farida; Cooke-Plagwitz Jessamine (Topics in Linguistics, 2020)
This research is conducted qualitatively and aimed at patterning and describing clause and sentence structure in Lampung language through the configuration of its constituents. Regarding the constituents, Lampung has two types of clause: minor and major clauses. A minor clause is indicated by only one constituent, which is commonly a subject, predicate or adjunct. Regarding its function, it can be classified as vocative, shown by exclamation (Wuy!, Huy!); a greeting, as shown by an expression (tabikpun ngalam pukha); and an Arabic greeting (assalamualaikum). On the other hand, a major clause minimally consists of a subject and predicate, and apart from these there can also be an object, complement and adverbial. Furthermore, this research finds various categories that can act as predicative constituents: they are a verb/verbal phrase, adjective/adjective phrase, and noun/nominal phrase. Additionally, a copular verb (iyulah) and existential marker (wat) can also be the predicate. This research also reveals that in a sentence two or more clauses are connected by a conjunction, and then this conjunction becomes an indicator of dependent clauses. Also, a dependent clause can be found after the subject or the object of the independent clause.